Gondolatok vállalati információs rendszerekről - Hampel, György (Jelenkori Társadalmi és Gazdasági Folyamatok, 2014)
Large and medium-sized enterprises cannot get along without an information system; these firms have become heavily computer-dependent. This paper briefly summarizes the possible needs and their reasons; it describes how the continuously developing information systems can be categorized based on their services; it covers the options enterprises have to implement such systems (to develop, to buy a standard system or to outsource). The paper also deals with the fact that when investing in an information system, return on investment is an important factor but the consequences of the lack of investment has to be considered as well. The final section covers some aspects of the enterprise systems and their influence on the enterprise competitiveness.